What to say next : successful communication in work, life and love with autism spectrum disorder - Nannery, Sarah; Nannery, Larry (Tiller Press, 2021)
"Using her personal experience living as a professional woman with Autism Spectrum Disorder, Sarah Nannery, together with her husband, Larry, offers this timely communication guide for anyone on the Autism spectrum looking to successfully navigate work, life, and love"--